Search for lepton-flavor violating decays B+ ->K+ [mu]+-e-+ - Aaij, Roel; Archilli, Flavio; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2019)
A search for the lepton-flavor violating decays B+→K+μ±e∓ is performed using a sample of proton-proton collision data, collected with the LHCb experiment at center-of-mass energies of 7 and 8 TeV and corresponding to an integrated luminosity of 3 fb−1. No significant signal is observed, and upper limits on the branching fractions are set as B(B+→K+μ−e+)<7.0(9.5)×10−9 and B(B+→K+μ+e−)<6.4(8.8)×10−9 at 90% (95)% confidence level. The results improve the current best limits on these decays by more than one order of magnitude.
LHCb Collaboration: R. Aaij, F. Archilli, P. D'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecná, B. Leverington, H. Malygina, J. Marks, D. Mitzel, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, S. Stemmle, U. Uwe [und viele weitere]
Gesehen am 05.05.2020
Im Titel sind "+" und "±" und "minus plus" hochgestellt